Evaluation of antibacterial activity of neolamarckia macrophylla leaf extract - Izzarul Atirah, binti Boestamam (Universiti Malaysia Sarawak (UNIMAS), 2016)
Tremendous research were done to extract bioactive compound from natural product especially plant which can be used as an alternative drugs to treat infection. The evaluation of atntibacterial activity of Neolamarckia macrophylla leaves crude extract by using three method: maceration, Soxhlet and direct use was determined using disc diffusion method against medically important baceria such as Escherichia coli, Klebsiella sp., Pseudomonas aeruginos, Salmonella typhimuriu,, Listeria monocytogenes, Staphylococcus aureus and Bacillus cereus with different concentration (12.5%, 50%, 75% and 100%). The results showed that the inhibition growth varies among tested bacteria with maceration method gives better result compared ot other techniques used. Two solvents were used; ethanol and distilled water, and ethanol extradtion has better antinacterial acivity compared to aqueous extraction. This study provides preliminary results suggestisng that N. macrophylla can be used as a source of drug to fight infection.